A synthetic intron in a naturally intronless yeast pre-tRNA is spliced efficiently in vivo. - Winey, M (1989)
Saccharomyces cerevisiae glutamine tRNA(CAG) is encoded by an intronless, single-copy gene, SUP60. We have imposed a requirement for splicing in the biosynthesis of this tRNA by inserting a synthetic intron in the SUP60 gene. Genetic analysis demonstrated that the interrupted gene produces a functional, mature tRNA product in vivo.